(untitled) (Journal of Hama University, 2022)
The xylanase is one of the enzymes that is characterized by various industrial applications, the most important of which are biofuels, feed, food industries, and paper. In this study, the optimal conditions for the production of xylanase by (Trichoderma viride) using response surface methodology, using an agricultural weed, (Prosopis juliflora), A Central Composite Design was used to investigate the effects of four independent variables: pH, concentration pods (w/v %), concentration sucrose(%),concentration yeast extract(%), on the response factor, xylanase activity (UI/mL), The independent variables were at three levels and their actual values selected on the basis of preliminary experimental results. A second-order polynomial model was used for predicting the response. Regression analysis showed that the variation was explained by the model. The optimal conditions for xylanase activity were found to be pH=6.5, concentration pods 4.6 (w/v %), concentration sucrose 0.3(%),concentration yeast extract 0.4(%), Under the optimum conditions the corresponding predicted response value for xylanase activity was 122.9 UI/mL. The good agreement between predicted and experimental values indicated suitability of the model employed and the success of response surface methodology in optimizing the xylanase activity.